A unique method for detecting beef tenderness based on viscoelasticity principle. Issue 5 (14th March 2017) - Long, Yuan; Tang, Xiuying; Wang, Wenjuan; Peng, Yankun; Dong, Xiaoguang; Kang, Xilong; Li, Yongyu
Abstract: Tenderness is an important parameter for evaluating textural properties of beef. Viscoelasticity is a comprehensive property of viscosity and elasticity. Detection of beef tenderness based on beef viscoelasticity could avoid sample destruction inherent to the traditional evaluation method. This study has built a novel detection system using an air flow supply and laser displacement sensor to evaluate beef viscoelasticity, collecting measurements of beef sample deformation from the air flow, and of the subsequent recovery occurring during a 12‐second time period. Compression curves and recovery curves were fitted by exponential function. The maximum compression deformation, d1, the recovery deformation, d2, and the total deformation, d3, were calculated. Instantaneous deformations of L1 and L2 were evaluated, including deformation areas of S1 and S2, respectively. The deformations for the period from 8 to 12 s were fitted by linear regression. Principal component analysis was used to find optimal principal components. Partial least squares regression method was used to build a model to predict the validation set. The optimal model was obtained using 12 principal components. Correlation coefficient and root mean square error of calibration set were 0.8541and 5.9727, respectively. Similarly, correlation coefficient and root means square error of validation set were 0.8357, respectively. The results showed that beef tenderness detection based on viscoelasticity can be of great value for practical application. This research provides a unique method for nondestructive and quantitative detection of meat and poultry. Practical applications: Tenderness is of great importance while evaluating the quality of beef. However, there is a lack of effective nondestructive methods to measure beef tenderness. A new method was developed to evaluate beef tenderness by applying air flow pressure on a beef sample surface and using a laser displacement sensor to measure the associated surface deformation as influenced by the beef viscoelasticity. The relationship between beef tenderness and the deformation was established so that the former can be predicted by observed deformation, thus, resulting in a unique method for evaluating beef tenderness.